CO2 methanation over supported monometallic and bimetallic oxide catalyst: a review / Muhammad Ezad Shafiq Mohd Tarmizi and Siti Aminah Md Ali - Mohd Tarmizi, Muhammad Ezad Shafiq; Md Ali, Siti Aminah (2020)
Rapid industrialization occurred during the 19th century caused a large quantity of CO2 to be emitted from different sources into the atmosphere. In order to reduce CO2 emission across the globe, various kinds of discoveries have been reported by researchers to convert CO2 into less hazardous substances by using a different combination of metal and support materials. Therefore, this research work aims to provide an informative review regarding the role of metals, supports and addition of secondary metal (promoters) to produce high-performance CO2 methanation metal catalyst. Specific emphasis is placed on the role of metals as well as on the role of supports as these are the most important factors which could contribute to the enhancement of CO2 methanation metal catalysts. In this research work, recent findings within the related scope from various researchers are thoroughly reviewed and the important data gathered are presented in the form of tables. Next, any significant trends obtained from the data are explained with reasonable scientific justifications. From the research conducted, Ni was chosen as the best material mainly due to its high methanation activity, wide usage in commercial applications and exhibit a high prospect for catalytic improvement. Next, the addition of secondary metal to existing metal catalyst especially Ce not only modify and reconstruct the catalyst structure but promote the reducibility of active species thus producing new catalyst with enhanced catalytic properties. From the findings, it can be clearly seen that the bimetallic catalyst has much higher catalytic performance compared to the monometallic catalyst because of the benefits offered by the second metal. From this research, conventional metal oxide support (Al2O3 & CeO2) was determined to exhibit better catalytic performance compared to other support materials due to its high specific surface area and high hydrogen storage ability.